235k views
25 votes
Solve:

(√x + 2)(√x - 2) = 0

x = ?

2 Answers

8 votes

Answer:


x=4

Explanation:

(√x + 2)(√x - 2) = 0

√x × √x - √x · 2 + 2 · √x - 2 · 2 = 0

√xx - 2 × √x + 2 · √x - 4 = 0

√x^1+1 - 2 · √x + 2 × √x - 4= 0

√x² - 2 · √x + 2· √x - 4 = 0

x^2/2 - 2 × √x + 2 · √x - 4 = 0

x - 2· √x + 2 · √x - 4 = 0

x - 4 = 0

(x - 4) + 4 = 0

x - 4 + 4 = 0

x = 4

User Kwgoodman
by
4.7k points
3 votes

Answer: x = 4

Explanation:

(√x + 2)(√x - 2) = 0

√x*√x - 2√x + 2√x -4 = 0

x - 0 - 4 = 0

x = 4

User Youurayy
by
4.5k points